Antibacterial Activity of Robusta Coffee (Coffea Canephora) Husk Extract Against Enterococcus Faecalis and Phorphyromonas Gingivalis: In Vitro Study - Prasetya, Rendra Chriestedy; Fatimatuzzahro, Nadie; Ermawati, Tantin; Kristina, Shinta; Prabaningrum, Raden Rara Hanifa (Trends in Sciences, 2024)
Enterococcus faecalis is one of the bacteria that is commonly found in infected root canals, necrotic pulp and failure of root canal treatment, while Phorphyromonas gingivalis play a role in inducing periodontitis. Both bacteria can enter the blood circulation and lead to risk factors for systemic disease such as atherosclerosis. ChKM is the most widely used root canal sterilization, and also 0.2 % chlorhexidine mouthwash for long-term usage. It can destroy a potent cell and is allergenic. Developing an alternative material for root canal sterilization and mouthwash for plaque control is necessary. One of the alternative natural products that is predicted to have antibacterial effect is robusta coffee husk peels. This research aimed to investigate the antibacterial activity of robusta coffee (Coffea canephora) husk extract on E. faecalis and P. gingivalis. The robusta coffee husk was extracted using the maceration process with 96 % ethanol as the solvent. This research is an experimental laboratory, was tested by disk diffusion methods (Kirby-Baurer) using Gram-positive E. faecalis ATCC 29212 and Gram-negative P. gingivalis ATCC 33277 consisted of 6 groups: Aquadest as a negative control group, ChKM (for E.facecalis) and 0.2 % chlorhexidine (for P. gingivalis) as positive control, 4 treatment groups of coffee robusta husk extract with different concentrations there were 250, 250, 500, 750 and 1,000 mg/mL. The antibacterial effect was examined by measuring the clear zone around the disk paper. The results of this study proved the presence of antibacterial activity of coffee robusta husk extract against E. faecalis and P. gingivalis. The higher concentrations followed with a greater antibacterial effect. HIGHLIGHTS Robusta coffee husk extract (Coffea canephora) has an antibacterial property against Gram-positive and Gram-negative bacteria Robusta coffee husk was extracted using the maceration process, and disk diffusion methods (Kirby-Baurer) for antibacterial test Robusta coffee husk extract with a concentration of 1,000 mg/mL showed the greatest inhibition zone. The higher the concentration, the bigger inhibition zone appeared GRAPHICAL ABSTRACT